A new species and a new record of alpheid shrimps of the genus Salmoneus Holthuis, 1955 (Crustacea: Decapoda: Alpheidae) from Iran - Ashrafi, Hossein; Ďuriš, Zdeněk; Naderloo, Reza (Zootaxa, 2020)
Extensive samplings of benthic fauna along the Iranian coastlines of the Persian Gulf and Gulf of Oman during 2018–2019 resulted in a small series of shrimps of the alpheid genus Salmoneus. Based on a thorough examination of this material, as well as previously collected specimens, one new species, S. rashedi n. sp., is described, whilst a significant range extension of S. chadwickae Ďuriš & Horká, 2016 is reported. Salmoneus rashedi n. sp. is a member of S. gracilipes species group. The present new species differs from other species of the group by a longer rostrum with a short dorsal crest and a single ventral rostral tooth; the species occurs in two colour forms from yellow to reddish orange with some transverse red bands.